The Effect of Health Education on Knowledge of Junk Food among Elementary School Students - Qurnia Latifah; Indri Puji Lestari; Rezka Nurvinanda (Inspirasi Foundation, 2026)
Introduction: The high consumption of junk food among children is a serious issue due to its negative health impacts, such as obesity, diabetes, and metabolic disorders from an early age. Fast food is popular for its convenience and taste, but it is low in nutrition. National and international data, including from the WHO and Riskesdas, show that junk food consumption among schoolchildren continues to increase, including in Bangka Belitung. Children's low knowledge about healthy food requires intervention in the form of health education. Objective: This study aims to determine the effect of health education on knowledge about junk food among fifth-grade students at Madrasah Ibtidaiyah Al Islam Kemuja in 2025. Method: This study used a quantitative pre-experimental research design with a one-group pretest-posttest approach, involving 70 students through total sampling. The instrument was a closed-ended questionnaire with indicators for the definition, types, dangers, selection factors, and prevention of the impacts ofjunk food. Analysis used a paired t-test. Result: The results showed a significant increase in students' knowledge, from an average of 56.89 before the intervention to 76.27 after the intervention, with a significance value of 0.000 (<0.05). Conclusion: This study concludes that health education significantly improves students’ knowledge regarding junk food. These findings highlight the important role of structured educational interventions in promoting healthy dietary awareness among school-aged children. Therefore, healthcare institutions may use these results as a reference for developing and implementing regular school-based health promotion programs. Educational institutions can also utilize this study as supplementary learning material and as a reference in academic resources.